A Test of Minority Stress Theory With Asian Americans. (October 2022) - Lei, Nina; Velez, Brandon L.; Seoud, Judy M.; Motulsky, Wei N.
The present study extended minority stress theory by testing the associations of racist stressors (racist discrimination, expectations of rejection, and internalized racism) and maladaptive coping strategies (internalization and detachment) with psychological distress and psychological well-being. In addition, expectations of rejection, internalized racism, internalization, and detachment were tested as mediators of the racist discrimination–mental health link. Data were analyzed from 297 Asian American adults. Results indicated that greater levels of all racist stressors and maladaptive coping strategies were each associated with poorer mental health at the bivariate level, but only internalization and detachment were unique predictors of distress and only internalized racism and detachment were unique predictors of well-being. Internalization and detachment mediated the positive indirect association of racist discrimination with distress, and detachment mediated the negative indirect relation of racist discrimination with well-being. Implications of the findings for practice, advocacy, education, training, and research with Asian Americans are discussed.